Newspaper microfilming : a plea for newsprint documentation - Majumdar, Gopal Kumar, 1930- (Firma K. L. Mukhopadhyay, 1974)
On the history and process of microfilming newspapers; includes a list of South Asian newspapers and periodicals on microfilm.